Photovoltaic system for the treatment of surface water polluted with polycyclic aromatic hydrocarbons in Colombia (2018)
Due to the development limitations of remote and non-interconnected zones related to the access to safe drinking water and taking into account the high electrical costs associated to the application of advanced oxidation processes (AOPs) for decontaminating water, the utilization of a photovoltaic (PV) array supplying the electrical needs of the technologies involved in the water treatment might be an alternative option. In this way, the current study presents the feasibility of using a PV array without batteries coupled to a UV/H2O2 system to treat surface water from a Colombian reservoir polluted with ultratrace levels of polycyclic aromatic hydrocarbons. Very promising results were obtained, with removal efficiencies near 100% and without the formation of by-products more dangerous than the parent contaminants. The results were comparable to those ones obtained using the conventional electrical grid. Consequently, the PV array evaluated allows the sustainable decontamination of pollutants in surface water persistent to traditional water treatments, with the subsequent production of drinking water, providing the accomplishment of other regulated parameters, in remote and non-interconnected areas, which are particularly important in developing countries, such as Colombia. Key words Renewable energy, photovoltaics, advanced oxidation process, water decontamination, non-interconnected zone